The Main Name System: An exercise in centralized computing - Deegan, Tim; Crowcroft, Jon; Warfield, Andrew (ACM SIGCOMM CCR, 2005)
Naming is a critical component of the internet architecture, and one whose complexity is often overlooked. As a global system, the DNS must satisfy millions of requests per second, while allowing distributed, delegated administration and maintenance. In this paper, we consider the design of the DNS and the widely distributed manner in which DNS records are published. We propose that the robustness and performance of the existing DNS could be dramatically improved by moving towards a centralized architecture while maintaining the existing client interface and delegated administration.